Reseña bibliográfica: Fuentes del Derecho Internacional: Casos y Prácticas - Laborias, Alexis Rodrigo (2022)
"Sources of International Law: Cases and Practices is a collective work, directed by Claudia G. Gasol Varela and coordinated by Natalia A. Pérez, who are also authors, along with Florencia Arbizu, Alan Feler, Marcos López Bustamante, Jorge Fernando Pared Mella, and Stephanie Villarreal Zogbi. The book has a foreword by Dr. Lilian del Castillo, Full Professor Consultation of Public International Law of\nthe Faculty of Law of the University of Buenos Aires...."